Effectiveness of Group Activity Therapy: "Family Gathering", to Ensure Family in Caring for Housing Disorders and Preventing Health - Wien Soelistyo Adi; Sri Eny Setyowati (Journal Research of Social Science, Economics, and Management, 2022)
Mental health problems in the community originate from three main things. The first is the public's understanding of the lack of knowledge about mental disorders, the second is the stigma about mental disorders that develops in the community and the last is the uneven distribution of mental health services. The purpose of this study was to apply Group Activity Therapy: "Family Gathering", to empower families in dealing with mental disorders at home and preventing relapses. The research method is a quasi-experimental design pre post intervention sample taken from families who have members with mental disorders in the city of Semarang with a total of 30 respondents. The results of the research analysis using the pair T test with statistical test results as follows: the details of the variables before and after the intervention are as follows: knowledge of P value of 0.787 no difference, P value of attitude 0.489 no difference, self-efficacy P value of 0.018 no difference, family role P value 0.000 there is a difference, independence. P value 0.813 no difference. So it can be concluded that the application of Group Activity Therapy: "Family Gathering", to maintain family care in treating mental disorders at home and preventing recurrence, namely from knowledge of attitude and independence there was an increase but not significant with P value > 0.005, while self-efficacy and mentoring family there is a significant difference with the P value <0.05.